Capacitance-voltage and conductance-voltage characteristics of Ag/n-CdO/p-Si MIS structure prepared by sol-gel method - Karatas, S.; Yakuphanoğlu, Fahrettin; Amanullah, F. M. (Pergamon-Elsevier Science Ltd, 2012)
The frequency dependent electrical properties of Ag/n-CdO/p-Si structure has been investigated using capacitance-voltage (C-V) and conductance-voltage (G/omega-V) characteristics in the frequency range 10 kHz-1 MHz in the room temperature. The increase in capacitance at lower frequencies is observed as a signature of interface states. The presence of the interfaces states (N-ss) is also evidenced as a peak in the capacitance-frequency characteristics. Furthermore, the voltage and frequency dependence of series resistance were calculated from the C-V and G/omega-V measurements and plotted as functions of voltage and frequency. The distribution profile of Rs-V gives a peak in the depletion region at low frequencies and disappears with increasing frequencies. The values of interface state densities and series resistance from capacitance-voltage-frequency (C-V-f) and conductance-voltage-frequency (G/omega-V-f) measurements were obtained in the ranges of 1.44 x 10(16)-7.59 x 10(12) cm(-2) eV(-1) and 341.49-8.77 Omega. respectively. The obtained results show that the C-V-f and G/w-V-f characteristics confirm that the interface states density (N-ss) and series resistance (R-s) of the diode are important parameters that strongly influence the electrical parameters in Ag/n-CdO/p-Si structures. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Interfaces; Oxides; Electronic materials; Sol-gel growth; Electrical properties